Modelos computacionais avançados aplicados na adsorção multicomponente de fármacos - Pauletto, Paola de Souza (2022)
Pharmaceutical compounds are fundamental to the preservation of human and animal health. However, its high and continuous consumption, associated with its incorrect disposal and the inefficient treatments of water and effluents, can cause significant damage to the environment and human health. Besides, real waters and effluents are characterized by a mixture of different chemical contaminants, which makes their treatment even more challenging. The adsorption technique on activated carbon was used to simultaneously remove nimesulide and paracetamol present in aqueous solutions. The objective of this work was to apply advanced mathematical models to predict the adsorption behavior, due to the complexity between the adsorbent-adsorbate interactions. First, an artificial neural network was successfully trained and optimized to simultaneously predict the single and binary adsorption of these pharmaceuticals as a function of the operating conditions: adsorbent particle size, adsorbent dosage, initial pharmaceutical concentration, and contact time. The highest adsorption capacities were found for the adsorbent dosage of 0.5 g/L, particle size of 150 μm, and 300 minutes of contact time. In sequence, the adsorption equilibrium was evaluated through different isotherm models, in which the Langmuir isotherm satisfactorily fitted the single adsorption equilibrium of nimesulide and paracetamol, while the Extended Langmuir isotherm better adjusted the binary adsorption equilibrium of these pharmaceuticals on activated carbon. The physisorption process was exothermic, reaching higher adsorption capacities at 298 K. Finally, the Pore Volume and Surface Diffusion Model (PVSDM) could be extended and applied, for the first time in the literature, to multicomponent adsorption systems. The proposed model was called Extended PVSDM and the finite difference approximation technique was successfully applied to its numerical solution. The results showed that there was no dominance of a sole adsorption mechanism, but both external mass transfer and intraparticle diffusion played an important role during adsorption. Overall, the experimental results showed a higher affinity of activated carbon for nimesulide, reaching an adsorption capacity of 196.32 mg/g against 58.21 mg/g for paracetamol. During the binary adsorption, this greater selectivity towards nimesulide caused a significant competition with paracetamol molecules, suppressing the adsorption of paracetamol (25.80 mg/g) and promoting the adsorption of nimesulide (199.49 mg/g) in the active sites of activated carbon. The characterization of the adsorbent before and after adsorption suggested that paracetamol interacted with the active sites of carbon through hydrogen bonds, while nimesulide interacted through hydrogen bonds and π-π and n-π dispersive interactions.